Integrated Management of Key Pests in Edamame Cultivation: Harnessing Biological Agents and Botanical Pesticides - Haryadi, Nanang Tri; Kurnianto, Agung Sih; Dewi, Nilasari; Natasyah, Defi Cindi; Oktaviani, Nabiila Salsabil; Saputro, Puguh Widianto; Putri, Rizka Adelia; Ruchma, Verdiana Wahyu Hidayati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Edamame (Glycine max L. Merr.) is a high-value crop and an export commodity with very high environmental qualification standards. Spodoptera litura and Bemisia tabaci reduce both the quantity and quality of production. Therefore, more environmentally friendly pest control methods are needed. This study evaluated several biological control agents. A field experiment was conducted using a Randomized Block Design with eleven treatments across three locations. The treatments included entomopathogenic fungi (Beauveria bassiana and Metarhizium anisopliae), Bacillus thuringiensis, Trichogramma sp., a botanical pesticide (1% azadirachtin), and light traps. All treatments were applied during the flowering stage. Spraying was carried out once a week, and parasitoids were released every two weeks. The results showed that pest populations changed over the observation period. The population of B. tabaci decreased from week 4 to week 7, along with increased rainfall and enhanced effectiveness of the fungus. Treatments with combined biological agents with light traps produced highly consistent reductions in pest populations. This suggests that multiple integration of biological agents and physical traps provides stable pest suppression. Future optimization is more promising in terms of timing and long-term validation related to edamame management.